PENGARUH CURRENT RATIO DAN DEBT TO EQUITY RATIO TERHADAP RETURN ON ASSETS PADA PT MUSTIKA RATU TBK PERIODE 2013-2022 - Maulidiah, Eka; Janudin (Journal of Research and Publication Innovation, 2024)
The purpose of this research is to determine the influence of the Current Ratio and Debt to Equity Ratio on Return on Assets at PT Mustika Ratu, Tbk either partially or simultaneously. The method used is a quantitative method. The sample used is the financial report of PT Mustika Ratu, Tbk for 10 years, namely the 2013- 2022 period. The analysis method used in this research is multiple linear regression analysis. Data analysis uses the SPSS version 26 software application. Data analysis uses the classic assumption test, regression analysis, correlation coefficient analysis. Analysis of the coefficient of determination and hypothesis testing. The results of this research are that the Current Ratio has a significant effect on Return on Assets with a coefficient of determination value of 0,19% and the hypothesis test shows that the calculated t value > t table or (0.442 > 5.14), this is also confirmed by the p value < Sig. 0,05 or (0,001 < 0,05). Debt to Equity has a significant effect on Return on Assets with a coefficient of determination value of 71% influenced by other factors. Hypothesis testing obtained t count > t table or (-,783 < 2306). This is also confirmed by the p value < Sig. 0,05 or (0,456 > 0,05).